Ordering chaos : regulating the internet - Ang, Peng Hwa (Cengage Learning Asia, 2020)
Provides an expansive view of Internet regulation, including the deployment of technology, the use of market forces, the formulation of industry self-regulation as well as legislation. Takes evidence from real-life cases and uses them to explain regulatory approaches and paradigms.